2014
DOI: 10.1080/10911359.2014.848679
|View full text |Cite
|
Sign up to set email alerts
|

Arab American Marriage: Culture, Tradition, Religion, and the Social Worker

Abstract: The growing and varied Arab American population and the continuing stereotyping and mistrust between people of Arab descent and other Americans make the need for culturally competent social work more pronounced. This study considers the importance the institutions of marriage and family retain within what can be a generally high-context community. Marriage, family, and religious relationships can be complicated by a sense of honor and stigma alongside frequently distressing experiences or news from the country… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 49 publications
(151 reference statements)
0
7
0
Order By: Relevance
“…The complex relations between patriarchy, religion, tradition, and culture reinforce oppression against women (Aghtaie, 2016; Douki, Nacef, Belhadj, Bouasker, & Ghachem, 2003). While religion, tradition, and culture often interact with each other and at times will be indistinguishable (Woodhead, 2011), for the purposes of this article, we are defining religion as formalized beliefs, values, and institutional practices in which a divine being or supernatural presence is integral (Bruce, 2011); tradition as pertaining to ideas and practices that have been become established over time (Kopff, 2015); and culture as pertaining to expectations and norms within a social context (Al-Krenawi & Jackson, 2014).…”
mentioning
confidence: 99%
“…The complex relations between patriarchy, religion, tradition, and culture reinforce oppression against women (Aghtaie, 2016; Douki, Nacef, Belhadj, Bouasker, & Ghachem, 2003). While religion, tradition, and culture often interact with each other and at times will be indistinguishable (Woodhead, 2011), for the purposes of this article, we are defining religion as formalized beliefs, values, and institutional practices in which a divine being or supernatural presence is integral (Bruce, 2011); tradition as pertaining to ideas and practices that have been become established over time (Kopff, 2015); and culture as pertaining to expectations and norms within a social context (Al-Krenawi & Jackson, 2014).…”
mentioning
confidence: 99%
“…In Arabic Jordanian society males are dominant and any discussions about sexual relationships can lead to being labelled as sexually disabled, thus affecting their social position [ 19 ]. Hence, Arab males avoid discussions about sexual relationships or need to maintain an acceptable social status in their community [ 20 ]. This is aligned with the studies by Alananzeh et al and Butow et al who reported a low level of sexuality unmet needs which may reflect the taboo nature of discussing sexual needs [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, it is possible that the relationship between mental disorder and subsequent marriage formation may differ for different groups of migrant women. In predominately patriarchal societies such as South Asia, marriage may be important for acceptance and status in the community, particularly for women ( Al-Krenawi & Jackson, 2014 ; Sharma et al, 2013 ). Thus, there may be more pressure to find and accept a partner regardless of their attractiveness in terms of age or socioeconomic or health status.…”
Section: Introductionmentioning
confidence: 99%